2023
DOI: 10.1111/sji.13255
|View full text |Cite
|
Sign up to set email alerts
|

The adaptation model of immunity: A new insight into aetiology and treatment of multiple sclerosis

Abstract: Current research and drug development for multiple sclerosis (MS) is fully influenced by the self–nonself (SNS) model of immunity, suggesting that breakage of immunological tolerance towards self‐antigens expressed in the central nervous system (CNS) is responsible for pathogenesis of MS; thus, immune suppressive drugs are recommended for the management of the disease. However, this model provides incomplete understanding of the causes and pathways involved in the onset and progression of MS and limits our abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 127 publications
(249 reference statements)
0
0
0
Order By: Relevance
“…Such tissue-based activation of the immune response is evident from the presence of tissue-resident T memory cells (Trm) 54 which can be explained by the quantum model of T cell activation recently proposed by the last author 55 . Also, the primary function of immune responses has been proposed to be participating in homeostasis of their target cells [56][57][58][59][60][61] . This homeostatic function can explain the observations on inability of auto-reactive T cells to induce autoimmune pancreatitis following adoptive transfer of OVA-specific T cells that recognized and became activated by OVA-expressing pancreas 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Such tissue-based activation of the immune response is evident from the presence of tissue-resident T memory cells (Trm) 54 which can be explained by the quantum model of T cell activation recently proposed by the last author 55 . Also, the primary function of immune responses has been proposed to be participating in homeostasis of their target cells [56][57][58][59][60][61] . This homeostatic function can explain the observations on inability of auto-reactive T cells to induce autoimmune pancreatitis following adoptive transfer of OVA-specific T cells that recognized and became activated by OVA-expressing pancreas 62 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these models are predicted upon the assumption that the main role of the immune system is to safeguard the host against invading pathogens and diseases. However, following an extensive review of the existing literature, we have recently posited that the immune system's principal function lies in its participation in maintaining tissue homeostasis 17,18 . This function is orchestrated by activated and effector immune cells that support haemostasis of their target cells, which differs from tissue homeostasis through checks and balances of immune cells or Newtonian action and reaction of effector and regulatory cells 19 .…”
Section: The Classic Models Of T‐cell Activation: the Sns/ins And Dangermentioning
confidence: 99%
“…Notably, studies involving RAG −/− mice, characterized by lymphocyte deficiency, have demonstrated correlations between impaired T‐cell‐dependent neurogenesis, compromised cognitive function, heightened anxiety‐like behaviour, and impaired stress response 23 . Consequently, alterations in target tissues that result in an intolerance of an ongoing immune response can lead to autoimmune diseases, effectively characterized as immune intolerance 17,18 . Recently, the first author proposed the term ‘immune intolerance’ as a more fitting nomenclature for the understanding of autoimmune diseases.…”
Section: The Classic Models Of T‐cell Activation: the Sns/ins And Dangermentioning
confidence: 99%
See 2 more Smart Citations